Temperature dependent partitioning mechanisms and its associated microstructural evolution in a CMnSiAl quenching and partitioning (Q&P) steel. (December 2021) - Maheswari, N.; Amirthalingam, Murugaiyan; Schwedt, Alexander; Brokmeier, Heinz Günter; Schell, Norbert; Mayer, Joachim; Kumar, K.C. Hari; Sankaran, S.
Abstract: The effect of temperature (350 °C ¡ M S ¡ 450 °C) on the partitioning mechanisms and the final microstructure evolution in a CMnSiAl quenching and partitioning (Q&P) steel was investigated. The microstructure of both the Q&P specimens, comprised of distorted BCC or pseudo tetragonal martensite structure with two different characteristics namely (i) tempered or carbon depleted martensite that formed during initial quenching (M f ¡ 240 °C ¡ M S ) and partitioning step and (ii) carbon enriched fresh martensite that formed after partitioning step and final quenching (RT) together with blocky and inter-lath films of retained austenite. In addition, packets of M/A constituents were observed in Q&P-350-1min specimen and some traces of carbide and plate martensite were observed in Q&P-450-1min specimen. The increase in partitioning temperature led to nearly 2% increase in the amount of retained austenite (both blocky and inter-lath) with increased carbon content of 0.27 wt.%. Along with carbon partitioning, slight interface mobility/isothermal martensite formation was also observed in the case of specimen partitioned at 350 °C, whereas tempering effect was predominantly seen in the case of specimen partitioned at 450 °C. Irrespective of the partitioning temperature, the amount of carbon required to stabilize the retained austenite at RT was found to be about 1.15 wt.% and was confirmed through APT analysis. Graphical abstract: Highlights: The CMnSiAl steel was subjected to below and above M S (Q&P) partitioning treatment. Tempered, fresh martensite having distorted BCC was evident with blocky/film RA. Slight interface mobility/isothermal martensite observed in below M S partitioning. Tempering of martensite with carbon partitioning occurred in above M S partitioning. Effective carbon partitioning led to retain stable austenite at RT with 1.15 wt.% C.